Relationship between nurses' knowledge about identification in patient safety and the accuracy of patient identification in the inpatient ward - Ika Puspita Sari; M. Malik Ibrahim; Ismawati - (UPPM STIKES Pemkab Jombang, 2025)
Accurate patient identification is a critical aspect of patient safety to prevent medical errors such as incorrect medication or treatment. This study aims to analyze the relationship between nurses' knowledge of patient identification and the accuracy of its implementation in the inpatient ward of Bangil Regional General Hospital. This quantitative cross-sectional study was conducted on 89 nurses at Bangil Regional General Hospital. Data were collected through a nurse knowledge questionnaire and observation of the accuracy of patient identification, then analyzed using the Chi-Square test. A total of 87.6% of nurses had fairly good knowledge about patient safety identification, while 11.2% had insufficient knowledge. Of the nurses with fairly good knowledge, 76.3% performed identification correctly and 2.7% incorrectly. Meanwhile, among nurses with insufficient knowledge, 0.3% performed identification accurately and 9.0% inaccurately. Statistical analysis showed a significant relationship between knowledge and the accuracy of patient identification (p-value = 0.032). Based on the results of the study, it can be concluded that there is a relationship between nurses' knowledge of patient identification and the accuracy of patient identification at Bangil Regional General Hospital. The recommendation that can be given is that continuous training and system reinforcement are needed to ensure consistent implementation of patient safety standards.